Chemical Mechanisms in the induction of cancer - Haddow,Alexander (London Royal Institiute of chemistry, 1959)
Fourth P.F.Frankland Memorial Lecture
Fourth P.F.Frankland Memorial Lecture
Keywords: chemical michanism -- introduction of cancer